Evaluation of Multi-Drug Resistant Tuberculosis Predictor Index in Surakarta, Central Java - Putri Pamungkas; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2018)
Background: Tuberculosis (TB) remains a global public health problem. New cases of lung Tuberculosis in 2015 were 10.4 million worldwide. One of the challenging in TB control to be addressed is the development of Multi-Drug Resistant Tuberculosis (MDR-TB). There were an estimated 15,380 TB cases in Indonesia by 2015 with 1,860 positive TB cases and 1,566 cases successfully treated. This study aimed to determine the predictor index for MDR-TB.Subjects and Method: This was an analytic observational study with a case-control design. The study was conducted at Dr. Moewardi Hospital, Surakarta, Central Java, from August to November 2017. The study subjects were selected by fixed disease sampling including 75 MDR-TB patients and 75 TB patients. The dependent variable was MDR-TB. The independent variables were medical history, co-morbidity (Diabetes Mellitus), drug side effect, drug-taking supervisor, and regularity of treatment. The data were collected by questionnaire and medical record. The data were analyzed by a multiple logistic regression.Results: MDR-TB Occurrence Index increased with drug-taking supervisor (b = 2.33; 95% CI= 3.83 to 27.91; p<0.001), drug-side effect (b = 0.73; 95% CI= 0.58 to 7.45; p=0.026), medical history (b = 2.35; 95% CI= 3.80 to 29.38; p<0.001). MDR-TB Occurrence Index decreased by absence of type 2 Diabetes Mellitus (b = -0.56; 95% CI= 0.18 to 1.78; p= 0.033), regular treatment (b = -1.73; 95% CI= 0.06 to 0.46; p<0.001).Conclusion: MDR-TB Occurrence Index is determined by the drug-taking supervisor, drug side effect, medical history, Type 2 Diabetes Mellitus, and regular treatment.Keywords: MDR-TB Occurrence Index, medical history, drug-taking supervisor, drug side effect, Type 2 Diabetes Mellitus, regular treatmentCorrespondence: Putri Pamungkas. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java. Email: pamungkasputri95@gmail.com.Journal of Epidemiology and Public Health (2018), 3(2): 263-276https://doi.org/10.26911/jepublichealth.2018.03.02.06